Appropriateness of hip osteoarthritis management in clinical practice compared with the American Academy of Orthopaedic Surgeons (AAOS) criteria - Eslam Alkaramany (14150658) (2022)
Purpose The American Academy of Orthopaedic Surgeons (AAOS) developed the appropriate use criteria (AUC) for the management of hip osteoarthritis (OA) to guide surgeons in making decisions based on the best available evidence. This study aimed to assess the applicability of the AUC by comparing the actual treatment provided at our institution with the AUC recommendations. Methods A retrospective review of 115 patients who were diagnosed and treated for hip OA at our institution between December 2017 and December 2019 was performed. Data were collected and entered into the AUC application to determine the rate of appropriateness of the provided treatment according to the AUC recommendations. Then, the actual provided treatments were compared with the AUC recommendations to determine the agreement between the two. Results There were 115 patients, with a mean age of 50.08 years (range, 30–80 years). The most frequent patient characteristics were middle age (40–65 years) with function-limiting pain at moderate to long distances, minimal hip OA on X-ray examination, mild range of motion limitation, and presence of modifiable risk factors for negative outcomes. The overall rate of appropriateness and in agreement with the AUC recommendations was 100% for conservative treatments and 80.1% for surgical treatments. Conclusions This study shows that the majority of the hip OA treatments provided at our institution were appropriate and in agreement with the AUC recommendations. Furthermore, the AUC can be easily accessed through a free web application using a computer or smartphone to obtain the recommended treatment for any patient with hip OA. Other Information Published in: International Orthopaedics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00264-021-05150-x